Optimalisasi Identitas Visual Umkm Kerupuk Tahu Bagus Hasby Melalui Desain Logo Dan Kemasan Produk - Magdalena, Betty; Riyan Utama, Riyadini; De Yusa, Viola (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2025)
This community service program aims to optimize the visual identity of the Micro, Small, and Medium Enterprise (MSME) Kerupuk Tahu Bagus Hasby through the development of a more attractive and functional logo and product packaging design. The main issue faced by the partner is the absence of a consistent visual identity, which makes the product difficult to distinguish from competitors and reduces its market appeal. The implementation methods include field observation, interviews with the business owner, design needs analysis, and the creation of logo and packaging concepts based on appropriate graphic design principles. The results show that the new logo provides a more professional and recognizable brand image, while the redesigned packaging enhances aesthetic value, product information clarity, and overall marketability. The application of this visual identity also helps the partner strengthen branding efforts and expand product promotion. Thus, this community service activity contributes significantly to improving the visual quality and competitiveness of Kerupuk Tahu Bagus Hasby.